Aptamer-polymer functionalized silicon nanosubstrates for enhanced recovered circulating tumor cell viability and in vitro chemosensitivity testing - Shen QL (Dove Medical Press, 2016)
Qinglin Shen1,2,*, Caixia Peng2,3,*, Yan Zhan1, Liang Fan1, Mengyi Wang1, Qing Zhou4, Jue Liu2,4, Xiaojuan Lv1, Qiu Tang1, Jun Li1,2, Xiaodong Huang2, Jiahong Xia2 1Department of Oncology, 2Key Laboratory for Molecular Diagnosis of Hubei Province, 3Central Laboratory, 4Department of Pharmacy, The Central Hospital of Wuhan, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China *These authors contributed equally to this work Abstract: Selection of the optimal chemotherapy regimen for an individual cancer patient is challenging. The existing chemosensitivity tests are costly, time-consuming, and not amenable to wide utilization within a clinic. This limitation might be addressed by the recently proposed use of circulating tumor cells (CTCs), which provide an opportunity to noninvasively monitor response to therapy. Over the past few decades, various techniques were developed to capture and recover CTCs, but these techniques were often limited by a capture and recovery performance tradeoff between high viability and high efficiency. In this work, we used anti-epithelial cell adhesion molecule coated aptamer–poly (N-isopropylacrylamide) functionalized silicon nanowire substrates to capture and release epithelial cell adhesion molecule-positive CTCs at 32°C and 4°C, respectively. Then, we applied the nuclease to digest the aptamer to release the captured CTCs (near or at the end of the polymer brush), which cannot be released by heating/cooling process. High viability and purity CTCs could be achieved by decreasing the heating/cooling cycles and enzymatic treatment rounds. Furthermore, the time-saving process is helpful to maintain the morphology and enhance vitality of the recovered CTCs and is beneficial to the subsequent cell culture in vitro. We validated the feasibility of chemosensitivity testing based on the recovered HCC827 cells using an adenosine triphosphate–tumor chemosensitivity assay, and the results suggested that our method can determine which agent and what concentration have the best chemosensitivity for the culturing recovered CTCs. So, the novel method capable of a highly effective capture and recovery of high viability CTCs will pave the way for chemosensitivity testing. Keywords: circulating tumor cells, aptamer–PNIPAM coating, capture and recovery, cell culture in vitro, chemosensitivity testing